The physical environment matters: room effects on online purchase decisions - Eklund, Ann; Edenbrandt, Anna; Rahm, Johan; Johansson, Maria (Frontiers in Psychology, 2024)
Introduction People as individual consumers are regularly targeted in sustainability campaigns or communications with the hope of enhancing sustainable behavior at an individual level, with subsequent sustainability transformation at a larger societal scale. However, psychological motivation is complex and campaigns need to be based on an understanding for what individual, and contextual, factors support or hinder sustainable behavioral choices. Methods In a discrete choice experiment, participants made hypothetical online purchases in each of three rooms designed to evoke associations to hedonic, gain, and normative goal frames. Participants were shown a campaign message intended to prime sustainable textile consumption prior to the purchase. For each product (t-shirt or bananas) hedonic (comfort/look), gain (price), and normative (organic/ fairtrade) attributes were varied in an online choice experiment. Results Preferences for the normative attribute of t-shirts increased in the normative room compared to the room with gain associations. No effect of the rooms with hedonic or gain priming was observed on the choice. Discussion The study supports the hypothesis that the physical room can enhance goal frame activation and behavioral choice but concludes that such priming effect is sensitive to specificity of the prime.